The Jew in Seventeenth-Century Protestant Thought - Healey, Robert M. (Church history, 1977)
In his pamphlet entitled From the First to the Last of the Just, Jean-Paul Lichtenberg concludes a brief history of Jewish-Christian relations with a list of five periods to each of which he assigns a particular quality of anti-Judaism or anti-Semitism. Of the third period, 1096–1520, marked by the Crusades, the Ghetto and the Inquisition, Lichtenberg remarks,“the pogroms, the massacres and the persecutions perpetrated on the Jews by Christian hands are the manifestation of a Christian anti-Semitism of the people, fed by harsh and comtemptuous preaching. Doctrinal anti-Judaism had filtered down to the masses and given birth to anti-Semitism. The end of the Middle Ages and the beginning of the Renaissance brought about no changes in this situation. Relations between Christians and Jews are already poisoned and only the coming of the (French) Revolution will bring a change in the situation [emphasis added]. One may qualify the Christian anti-Semitism which prevails during this period as an anti-Semitism of passion based upon religion or, again, as an anti-Semitism of intolerance.”